The lambs of sheepfoot lane: Oldham Athletic AFC 1960–2023; football, politics and identity - O'Brien, James (Frontiers in Sports and Active Living, 2024)
The article focuses on an overview of the history, politics and cultural identity of Oldham Athletic AFC between 1960 and 2023. During this period the club, a founding member of the Football League, played across six divisions of the game's pyramid. My hometown club, the Latics faced an existential threat to its survival following relegation to the National League in 2022, before being rescued and brought back into local ownership on the long road back to its recapturing its former status. The successes of the Frizzell and Royle eras (1969–1994) contrast with the decline of the club in the 1960s, and its gradual meltdown since the mid—1990s. These are interwoven with the economic, geopolitical and cultural dynamics of the game. The study locates the history of a small club geographically positioned within the vortex of the of the two Manchester giants and Liverpool, in English football's traditional hinterland of the industrial north west. The article has four main themes. Firstly, it examines Oldham Athletic as custodian of local identity, fusing folkloric rituals within the club's historic and contemporary nexus. Secondly, it contextualises the interface between global, glocal and grobal forces impacting on tradition, modernity and post- modernity in the club's lexicon. It then considers the themes of ownership, commodification and globalisation, debating whether Oldham Athletic stands as a bastion of anti- globalisation, or reconfirms existing global patterns at the micro level, incorporating salient theoretical perspectives in this analysis. Finally, the review evaluates whether the political and social class cleavages of the club's roots in Oldham's late Victorian industrial landscape still resonate, or if they have been marginalised by socio- economic changes since 1960.